8-Epidiosbulbin E acetate triggers apoptosis via metabolic activation-mediated crosstalk between mitochondria and endoplasmic reticulum - Shiyu Zhang; Bowen Gong; Rong Tan; Yufen Liao; Xin Wang; Xu Wang; Ying Liu; Ting Liu; Jun Luo; Weiwei Li; Jia Yu; Ying Peng; et al. (Ecotoxicology and Environmental Safety)
8-Epidiosbulbin E acetate (EEA), a furan-containing diterpenoid lactone and key component of Dioscorea bulbifera L., has been found to induce notable liver injury in mice through CYP3A-mediated metabolic activation to a cis-enedial reactive metabolite. EEA exposure at 25, 50, 100, or 200 µM triggered apoptosis in cultured mouse primary hepatocytes, evidenced by alterations in mitochondrial and endoplasmic reticulum (ER) pathway protein levels. Pretreatment with ketoconazole, vitamin C, glutathione ethyl ester, or 4-phenylbutyric acid effectively reduced the apoptotic ratio and restored the balance of mitochondrial and ER pathway protein levels impacted by EEA in primary hepatocytes. In contrast, pretreatment with L-buthionine sulfoximine exacerbated the apoptotic ratio and altered protein levels associated with the mitochondrial and ER pathways induced by EEA. In summary, metabolic activation, GSH depletion, and ROS are implicated in the induction of apoptosis. EEA triggered apoptosis in cultured primary hepatocytes via disruption of the crosstalk between the mitochondrial and ER pathways.